A highly selective fluorescent probe for Zn2+ based on a rhodamine-6G dye derivative modified by a furan unit. (1st April 2018) - Qiao, Rui; Xiong, Wen-Zhang; Bai, Cui-Bing; Zhang, Lin; Zhu, Meng-Meng; Chen, Shui-Sheng; Miao, Hui
A fluorescent probe for Zn2+ based on rhodamine-6G has been synthesised. It showed excellent fluorescent specific selectivity and high sensitivity for Zn 2+ compared with other metal ions, such as Fe 3+, Cr 3+, Hg 2+, Ag +, Ca 2+, Cu 2+, Pb 2+, Cd 2+, Ni 2+, Co 2+ and Mg 2+, in CH3 CN–phosphate buffer saline solution. The distinct colour change and the rapid emergence of fluorescence emission provided 'naked-eye' detection of Zn 2+. The detection limit of the fluorescent probe towards Zn 2+ was 1.78 μM. In addition, the fluorescence lifetime and fluorescence quantum yield were measured.